THE INFLUENCE OF CONCENTRATION AND FREQUENCY OF PACLOBUTRAZOL TREATMENT OF MARIGOLD PLANTS - Sari Br. Ginting, Eva Indah; Darussalam, Darussalam; Budi, Setia (Jurnal Sains Pertanian Equator, 2019)
The aims of the study were to determine the best concentration, frequency and interaction of apifflied paclobutrazol to Marigold plants on alluvial soil. This research was conducted on the land of farmers in Banjar Laut Village, Rasau Jaya 2 District, Kubu Raya Regency, West Kalimantan Province from February 10, 2018 to April 12, 2018. The experimental used in this research was Factorial Randomized Complete Design (RCD) field method. with 2 treatment factors. The first factor was the concentration of spraying paclobutrazol with 4 levels of treatment (50 ppm, 100 ppm, 150 ppm, and 200 ppm) and the second factor was the frequency of spraying paclobutrazol with 3 levels of treatment (every 3 days, every 6 days, and every 9 days once) that is applied when the plants were planties. Thus, obtained 12 combinations with 3 replications and 3 samples. Variables observed in this study were plant height, leaf area, plant fresh weight, root volume, age of flowering, number of flower stalks, flower diameter, and flowers stalk length. The interaction between concentration and frequency significantly affected the variable of plant height and wet weight of the bottom. Single factor concentration of paclobutrazol significantly affected the root volume, total leaf area, age of flowering, flower diameter, and flower stalk length. The results showed that the interaction between 200 ppm concentration and frequency every 3 days produced a lower Marigold plant. In a single factor 100 ppm concentration paclobutrazol better affect root volume, upper wet weight, total leaf area, and flower diameter, while 200 ppm concentration better affect plant height, flowering age, and flower stalk length. Keywords: alluvial, marigold, paclobutrazol, growth retard